Assessing the Climate Change Adaptations of Upland Farmers: A Case of La Trinidad, Benguet, Philippines - Gerryc P. Alfonso (Indonesian Journal of Social and Environmental Issues (IJSEI), 2021)
Adaptation to climate change impacts varies from country to country. It is difficult to capture the concept of adaptations because it includes government policies and the behavior of farmers. Undertaking regional and local assessments of adaptations is still informative because it serves as baseline data for government and other institutions in supporting the needs of the farmers to adapt to the impacts of climate change. Thus, the study aims to look at the institutional supports availed and needed by farmers for climate change adaptation and assess their cost, effectiveness, institutional capacity, and acceptability. Personal interview and Focus Group Discussion complemented by various data gathering techniques was done to provide ample description and understanding of the sources, cost, effectiveness, institutional capacity, and acceptability of the climate change adaptations of farmers in La Trinidad, Benguet. Various institutional supports were given to the farmers but not equally and equitably distributed to the farmers. Almost all of the adaptations were effective, the cost and degree of institutional capacity needed are low but highly acceptable to the farmers.